"Replika Endemi" Resistensi PSAK 71 Sebagai Countercylical Terhadap Sustainability Perbankan Ditengah Pandemi - Nicholas Alexander Tungga; Melithasya Angelina; Elliza . (Jurnal Akuntansi, 2021)
Financial reports are important because they are useful for providing an overview for stakeholders in their decision making. Where in the preparation of financial statements the main regulation used is the Statement of Financial Accounting Standards (PSAK) established by the Indonesian Institute of Accountants (IAI) through the Financial Accounting Standards Board (DSAK). In the current status quo of Indonesia in facing the Covid-19 pandemic, the existence of PSAK has begun to be tested, adjustments must be made to financial accounting standards which are useful to strengthen the lines of corporate accountability in Indonesia and are able to answer the main urgency of Indonesia today, namely the weakening of the country's economy. The purpose of this paper is to produce a framework that can later become an alternative for banks in making decisions for implementing the PSAK 71 post model. The approach used in this paper is a qualitative approach by providing arguments and solutions for Indonesia's current economic conditions through the resulting framework design. After considering the aspects that affect the risk of bad credit, the conclusion is that PSAK 71 is able to trigger an economic upturn in Indonesia, because in its implementation it does not necessarily look at one aspect only but considers other aspects in responding to issues related to bad credit. Keywords: PSAK 71, Post Model Framework, Bad Credit, Indonesian Economy